External validity of randomised controlled trials in asthma: to whom do the results of the trials apply?. Issue 3 (14th November 2006) - Travers, Justin; Marsh, Suzanne; Williams, Mathew; Weatherall, Mark; Caldwell, Brent; Shirtcliffe, Philippa; Aldington, Sarah; Beasley, Richard
Abstract : Background: Asthma is a heterogeneous disease with a wide range of clinical phenotypes, not all of which may be encompassed in the subjects included in randomised controlled trials (RCTs). This makes it difficult for clinicians to know to what extent the evidence derived from RCTs applies to a given patient. Aim: To calculate the proportion of individuals with asthma who would have been eligible for the major asthma RCTs from the data of a random community survey of respiratory health. Methods: A postal survey was sent to 3500 randomly selected individuals aged 25–75 years. Respondents were invited to complete a detailed respiratory questionnaire and pulmonary function testing. Participants with current asthma were assessed against the eligibility criteria of the 17 major asthma RCTs cited in the Global Initiative for Asthma (GINA) guidelines. Findings: A total of 749 participants completed the full survey, of whom 179 had current asthma. A median 4% of participants with current asthma (range 0–36%) met the eligibility criteria for the included RCTs. A median 6% (range 0–43%) of participants with current asthma on treatment met the eligibility criteria. Interpretation: This study shows that the major asthma RCTs on which the GINA guidelines are based may have limited external validity as they have been performed on highly selected patient populations. Most of the participants with current asthma on treatment in the community would not have been eligible for these RCTs.